Immunotherapy or targeted therapy as the first-line strategies for unresectable hepatocellular carcinoma: A network meta-analysis and cost-effectiveness analysis - Liu, Kun; Zhu, Youwen; Zhu, Hong (Frontiers in Immunology, 2023)
Introduction: The existence of many phase III randomized controlled trials (RCTs) of first-line treatment for unresectable hepatocellular carcinoma (HCC) puzzle doctors and patients in choosing the most effective treatment strategies. We aimed to assess the efficacy, safety, and cost-effectiveness of immunotherapy or targeted therapy as the first-line strategy for unresectable HCC. Methods: The included clinical trials were retrieved from PubMed, Embase, the Cochrane library, and Web of Science databases, in which immunotherapy or targeted therapy was regarded as the first-line treatment for unresectable HCC, published in English between January 1, 2010, and September 20, 2022. We conducted a network meta-analysis (NMA) and cost-effectiveness analysis (CEA) from the Chinese payer’s perspective. Overall survival (OS), progression-free survival (PFS), the ranks of different treatments using P-score, and adverse events (AEs) were evaluated by NMA. Total costs, life-years (LYs), quality-adjusted life-years (QALYs), and incremental cost-benefit ratio (ICER) were estimated from 15-year Markov models developed by CEA. Results: We identified 2,825 records, including 11,796 patients, from 15 RCTs. The NMA revealed that sintilimab plus a bevacizumab biosimilar (HR, 0.57; 95% CI, 0.43 to 0.75; P = 0.96) and camrelizumab plus rivoceranib (HR, 0.56; 95% CI, 0.41 to 0.66; P = 0.94) could lead to great improvements in OS and PFS compared with sorafenib-related survival. The CEA indicated that tislelizumab increased by 0.220 QALYs (0.312 LYs) and decreased by $1,938 compared with sorafenib, which yielded ICERs of -$8,809/QALY (-$2,612/LY). Sensitivity analysis showed that the model was stable. Conclusion: Sintilimab plus a bevacizumab biosimilar and camrelizumab plus rivoceranib significantly prolonged OS and PFS, respectively. Further considering the pharmacoeconomics factors, tislelizumab is the most cost-effective first-line treatment strategy for unresectable HCC in China.